2006
DOI: 10.1002/sca.4950270106
|View full text |Cite
|
Sign up to set email alerts
|

Focused ion beam/scanning electron microscopy studies of Porcellio scaber (Isopoda, Crustacea) digestive gland epithelium cells

Abstract: The focused ion beam (FIB) was used to prepare cross sections of precisely selected regions of the digestive gland epithelium of a terrestrial isopod P. scaber (Isopoda, Crustacea) for scanning electron microscopy (SEM). The FIB/SEM system allows ad libitum selection of a region for gross morphologic to ultrastructural investigation, as the repetition of FIB/SEM operations is unrestricted. The milling parameters used in our work proved to be satisfactory to produce serial two-dimensional (2-D) cuts and/or thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…The main advantage of FIB-SEM imaging is permitting faster visualization of serial ultra-thin sections, which optimizes the adjustments needed for identification of the target structures (23,24). As a result, we confirmed that chondrocytes in the proliferative and the hypertrophic zones extend their short cytoplasmic processes to the cartilaginous fibrils that parallel the longitudinal axis of the growth plate, and that vesicular structures are present in the intercolumnar septa -even at the proliferative zone (Figs.…”
Section: Discussionsupporting
confidence: 70%
“…The main advantage of FIB-SEM imaging is permitting faster visualization of serial ultra-thin sections, which optimizes the adjustments needed for identification of the target structures (23,24). As a result, we confirmed that chondrocytes in the proliferative and the hypertrophic zones extend their short cytoplasmic processes to the cartilaginous fibrils that parallel the longitudinal axis of the growth plate, and that vesicular structures are present in the intercolumnar septa -even at the proliferative zone (Figs.…”
Section: Discussionsupporting
confidence: 70%
“…AFM and SEM are appropriate techiques to observe biological material [33,34]. By operating AFM in tapping mode we reduced the friction and adhesive force and enabled imaging of soft biological samples.…”
Section: Discussionmentioning
confidence: 99%
“…Instruments with this "slice-and-view" capability are available commercially, and have been used extensively to view the internal architecture of semiconductors and other solids (Giannuzzi et al, 2002;Giannuzzi and Stevie, 2005;Sugiyama and Sigesato, 2004). Preliminary efforts of the use of focused ion beam microscopy to view the internal structure of biological specimens have also been reported (Ballerini et al, 2001;Drobne et al, 2005;Gestmann et al, 2004;Heymann et al, 2005;Mulders, 2003;Young et al, 1993). Here, we report on our progress in applying dual beam imaging to biologically relevant samples at room temperature and at cryogenic temperatures.…”
Section: Introductionmentioning
confidence: 99%